Factorise 4b² + 16b ⇒ 4b(b+4)
expand (a-1)(a-2) ⇒ a(a-2) - 1(a-2) ⇒ a² - 2a - 1a + 2 ⇒a² - 3a + 2
factorise x² + 8x + 7 ⇒(x + 1) (x + 7)
evaluate y⁶ / y² ⇒ y * y * y * y * y * y / y * y = y⁴
if x = -1 and y = 5, find z when z = x² + 2y² ;
z = -1² + 2(5²) ⇒ 1 + 2(25) ⇒1 + 50 = 51
Make x the subject: y = 4x - 3
y = 4x - 3
<u>+3 +3</u>
3 + y = 4x
<u>÷4 ÷4 </u>
(3+y)/4 = x
Answer: (-9,4)
Step-by-step explanation:
2x-y=-22
-7x+y=67
-5x=45
x=-9
2(-9)-y=-22
-18-y=-22
-y=-4
y=4
Answer:
f(x)= -0.4x+107
Step-by-step explanation:
Answer:
The correct option is B
Step-by-step explanation: